Graphene Membranes for Multi‐Dimensional Electron Microscopy Imaging: Preparation, Application, and Prospect. (16th May 2022) - Gao, Xiaoyin; Zheng, Liming; Yao, Yating; Peng, Hailin
Abstract: Technological breakthrough in electron microscopy (EM) has started a resolution revolution in EM imaging. Nowadays, the promotion of resolution demands a robust background‐noise‐free EM support for specimen preparation, which is a primary bottleneck of high‐resolution EM imaging. Owing to the atomic thickness and excellent physical properties, graphene has attracted widespread attention in the EM field to achieve high‐resolution multi‐dimensional imaging. However, it is still challenging to prepare high‐quality suspended graphene membranes. Problems like breakage, contamination and wrinkling reduce the quality of suspended graphene membranes, which inhibit their wide and killer applications in EM imaging. In this review, suspended graphene membranes are looked deeply into for multi‐dimensional EM imaging. This study begins with a brief introduction to EM development, followed by a discussion of the synthesis of high‐quality graphene. Then it summarizes various approaches to produce suspended graphene membranes and their killer applications in multi‐dimensional EM characterization, including high‐resolution 2D imaging, cryo‐EM 3D reconstruction, and 4D in situ liquid EM. Based on current achievements, the prospects of graphene membranes for more cutting‐edge applications are finally proposed. Abstract : Graphene, owing to its excellent physical properties, has attracted widespread attention in the electron microscopy (EM) field to achieve high‐resolution multi‐dimensional imaging. In this review, the focus is on the synthesis of high‐quality graphene, various approaches to producing suspended graphene membranes, and killer applications in multi‐dimensional EM characterization. Prospects of graphene membranes for more cutting‐edge applications are also proposed.